The Effects of Whole-Body Vibration on the Cross-Transfer of Strength - Alicia M. Goodwill; Dawson J. Kidgell (The Scientific World Journal)
This study investigated whether the use of superimposed whole-body vibration (WBV) during cross-education strength training would optimise strength transfer compared to conventional cross-education strength training. Twenty-one healthy, dominant right leg volunteers (21±3 years) were allocated to a strength training (ST, m=3, f=4), a strength training with WBV (ST + V, m=3, f=4), or a control group (no training, m=3, f=4). Training groups performed 9 sessions over 3 weeks, involving unilateral squats for the right leg, with or without WBV (35 Hz; 2.5 mm amplitude). All groups underwent dynamic single leg maximum strength testing (1RM) and single and paired pulse transcranial magnetic stimulation (TMS) prior to and following training. Strength increased in the trained limb for the ST (41%; ES=1.14) and ST + V (55%; ES=1.03) groups, which resulted in a 35% (ES=0.99) strength transfer to the untrained left leg for the ST group and a 52% (ES=0.97) strength transfer to the untrained leg for the ST + V group, when compared to the control group. No differences in strength transfer between training groups were observed (P=0.15). For the untrained leg, no differences in the peak height of recruitment curves or SICI were observed between ST and ST + V groups (P=1.00). Strength training with WBV does not appear to modulate the cross-transfer of strength to a greater magnitude when compared to conventional cross-education strength training.